Post hoc analyses of East Asian patients from the randomized placebo-controlled PREVAIL trial of enzalutamide in patients with chemotherapy-naïve, metastatic castration-resistant prostate cancer. Issue 27 (July 2017) - Kim, Choung Soo; Choi, Young Deuk; Lee, Sang Eun; Lee, Hyun Moo; Ueda, Takeshi; Yonese, Junji; Fukagai, Takashi; Chiong, Edmund; Lau, Weber; Abhyankar, Sarang; Theeuwes, Ad; Tombal, Bertrand; et al.
Abstract: Background: Enzalutamide is an androgen receptor (AR) inhibitor that acts on different steps in the AR signaling pathway. In PREVAIL, an international, phase III, double-blind, placebo-controlled trial, enzalutamide significantly reduced the risk of radiographic progression by 81% (hazard ratio [HR], 0.19; P  < .0001) and reduced the risk of death by 29% (HR, 0.71; P  < .0001) compared with placebo in chemotherapy-naïve men with metastatic castration-resistant prostate cancer. Methods: To evaluate treatment effects, safety, and pharmacokinetics of enzalutamide in East Asian patients from the PREVAIL trial, we performed a post hoc analysis of the Japanese, Korean, and Singaporean patients. PREVAIL enrolled patients with asymptomatic or mildly symptomatic chemotherapy-naïve metastatic castration-resistant prostate cancer who had progressed on androgen deprivation therapy. During the study, patients received enzalutamide (160 mg/d) or placebo (1:1) until death or discontinuation because of radiographic progression or skeletal-related event and initiation of subsequent therapy. Centrally assessed radiographic progression-free survival (rPFS) and overall survival (OS) were coprimary endpoints. The secondary endpoints of the PREVAIL trial were investigator-assessed rPFS, time to initiation of chemotherapy, time to prostate-specific antigen (PSA) progression, and PSA response (≥50% decline). Results: Of 1717 patients, 148 patients were enrolled at sites in East Asia (enzalutamide 73, placebo 75). Treatment effect of enzalutamide versus placebo was consistent with that for the overall population as indicated by the HRs (95% confidence interval) of 0.38 (0.10–1.44) for centrally assessed rPFS, 0.59 (0.29–1.23) for OS, 0.33 (0.19–0.60) for time to chemotherapy, and 0.32 (0.20–0.50) for time to PSA progression. In East Asian patients, PSA responses were observed in 68.5% and 14.7% of enzalutamide- and placebo-treated patients, respectively. The enzalutamide plasma concentration ratio (East Asian:non-Asian patients) was 1.12 (90% confidence interval, 1.05–1.20) at 13 weeks. Treatment-related adverse events grade ≥ 3 occurred in 1.4% and 2.7% of enzalutamide- and placebo-treated East Asian patients, respectively. Conclusions: Treatment effects and safety of enzalutamide in East Asian patients were generally consistent with those observed in the overall study population from PREVAIL. ClinicalTrials.gov number: NCT01212991 Abstract : Supplemental Digital Content is available in the text